Perhitungan Kebutuhan Steam Pada Proses Pemisahan Minyak Pada Sludge Separator di Stasiun Klarifikasi Pabrik Kelapa Sawit PT. XYZ - Ratna Kristina Tarigan (JURNAL VOKASI TEKNIK, 2023)
Sludge separator is a tool used in the process of separating oil from sludge by adding hot water as a diluent used in the process of separating oil from sludge. Water is supplied to the hot water tank then steam is supplied with a temperature of 100 ⁰C and a pressure of 1.01 Bar to heat the water so that the expected water temperature is 90-95⁰C. In the sludge separator, sludge containing mud, oil, and water is fed from the buffer tank and hot water from the hot water tank which functions as a diluent, where in the sludge separator the oil is separated from the sludge by centrifugal force. After the separation process occurs in the sludge separator, the oil is separated from the sludge and flows into the oil reservoir and the sludge is collected into the waste pond. Based on mass balance calculations, it is obtained that the amount of water used in the process of separating oil in sludge in the sludge separator is 2,502.2501 Kg/hour. From the calculation of steam requirements, it is obtained that the amount of steam required in the process of separating oil in sludge in the sludge separator is 286.4361283 Kg/hour